The Perceived Impact of Online Student Evaluation to the Performance Among Faculty from PUP Branches and Campuses: Basis for Policy Review and Implementation - Reyes, J V; Ariraya, A C; Guerzon, R A; Solis, A L (KnE Social Sciences, 2018)
The study aims to determine the perception of the PUP faculty from branches and campuses about the student’s online evaluation and investigate the implication of results to their performance as teacher in higher education institution. Descriptive and inferential statistics were used to interpret data. The researchers utilized primary data through self-administered survey questionnaire and secondary data. Findings revealed that in general, the faculty find the content in four areas of evaluation namely: commitment, knowledge of the subject, teaching for independent learning and management, highly acceptable. They agree with the rating scale and its equivalent description. The perceived performance of the faculty in four areas showed improvement. The faculty recognized that their personal and social development had improved. When respondents were grouped according to highest educational attainment, significant difference was observed on commitment area. Majority of the faculty felt that students do not fully understand the content of the evaluation instrument, and worst, they use the evaluation as the chance to get even with the professors they dislike. It is recommended to simplify the statements in the instrument. To substantiate the comments and maintain objectivity, the researchers recommend inclusion of students’ personal assessment regarding learning. To further improve the performance of the faculty, deans and chairpersons may identify the administrative concerns of their faculty and identify areas that need training, retraining, coaching, and/or policy revision. Keywords: effective teaching, instruction, faculty performance, student evaluation